The Effect of Free Cash Flow, Leverage, Information Asymmetry, and Managerial Ownership to Profit Management - Nuriyah, Adinda Isna; Amir, Amir (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2023)
This study aims to examine the effect of free cash flow, leverage, information asymmetry, and managerial ownership on earnings management. The population in this study are mining companies that are listed on the Indonesia Stock Exchange in 2017-2020. The sampling method used purposive sampling and obtained 96 samples from 24 companies that met the criteria. Methods of data analysis using multiple regression analysis. The regression model has fulfilled the classical assumption tests (normality, multicollinearity, heteroscedasticity, autocorrelation), F and R2 tests and hypothesis testing using the T test. The results showed that (1) free cash flow has a positive effect on earnings management, (2) leverage has no effect on earnings management, (3) information asymmetry has no effect on earnings management, and (4) managerial ownership has no effect on earnings management.